Aesthetic rapture; the rasādhyāya of the Nāṭyaśāstra - Masson, J. Moussaieff (Jeffrey Moussaieff), 1941- (Deccan College building centenary and silver jubilee series, 1970)
On the concept of rasa in classical Indic poetics; study of the 6th chapter of Abhinavagupta's Abhinavabhāratī, 11th century Sanskrit commentary on Nāṭyaśāstra, classical treatise on drama and aesthetics by Bharata Muni.